New energy, new geopolitics : balancing stability and leverage - Ladislaw, Sarah O.; Leed, Maren; Walton, Molly A. (CSIS report., 2014)
This report evaluates the energy and geopolitical shifts that have arisen from the production of shale gas and light tight oil in the United States. It begins by assessing how much the unconventional energy trend has already impacted energy, geopolitics, and national security. The report then posits several possible energy futures that could emerge from the unconventionals revolution. Finally, it offers views on the major geostrategic question: how will the United States seek to utilize this, so far, domestic resource trend, and given the range of potential future energy outcomes, what might the geopolitical and national security implications be.